ANALISIS PEMBERIAN INSENTIF KEPADA INVESTOR ASING MENURUT UU NO. 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Prima Andari, Any; Wiryawan, I Wayan; Dewi Kasih, Desak Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
Indonesia needs funds from investors, especially foreign investors. Undeniably strongerforeign investment in terms of finance and technology because most of the foreigninvestor is a developed country. Indonesia currently needs funds to build the country'seconomy. Therefore, Indonesia needs foreign investors that the government through ActNo. 25 of 2007 on Investment provides more incentives to foreign investors to attractthem to invest in Indonesia and competition intensifies between countries. With theuncertainty of the law in Act No. 25 of 2007 on Investment makes foreign investors anddomestic investors reluctant to invest in Indonesia. With the enactment of Act No. 25 of2007 on Investment, known to the Indonesian government to protect national interests,the interests of investors in the country to develop a national industry.
Keywords: incentives; investors; investment